An Assessment of Customer Satisfaction with Digital Banking Services: A Case Study of the Bank of Commerce & Development, Benghazi (Comprehensive Journal of Science, 2025)
This study aimed to examine customer satisfaction with digital banking services provided by the Bank of Commerce & Development in Benghazi, Libya, where digital banking had become increasingly important for enhancing convenience and accessibility. A structured questionnaire was used to collect data from 187 respondents, and the results were analyzed using appropriate statistical methods. The findings revealed that perceived ease of use, perceived usefulness, trust, attitude toward the service, and convenience all had positive and significant influences on customer satisfaction. Although the study acknowledged certain limitations such as potential respondent bias and the possibility that some responses might not fully reflect actual opinions these limitations were not considered significant given the sample size. The results provided valuable implications and recommendations for policymakers, banking institutions, and future researchers to further improve digital banking services and enhance customer satisfaction.
Keywords: Digital Banking, customer satisfaction, Bank of Commerce & Development, Benghazi